2004
DOI: 10.1242/dev.00947
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic-dependent patterning of endothelin converting enzyme 1 expression and differentiation of impulse-conducting Purkinje fibers in the embryonic heart

Abstract: Impulse-conducting Purkinje fibers differentiate from myocytes during embryogenesis. The conversion of contractile myocytes into conduction cells is induced by the stretch/pressure-induced factor, endothelin (ET). Active ET is produced via proteolytic processing from its precursor by ET-converting enzyme 1 (ECE1) and triggers signaling by binding to its receptors. In the embryonic chick heart, ET receptors are expressed by all myocytes, but ECE1 is predominantly expressed in endothelial cells of coronary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
92
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 75 publications
8
92
2
Order By: Relevance
“…The recruitment of cardiomyocytes into the Purkinje fiber system has been demonstrated to be related to hemodynamic influences derived from the coronary vasculature and endocardial lining of the ventricular lumen Hyer et al, 1999), with mature ET-1 and the ECE1 metalloprotease as key inductive factors (Takebayashi-Suzuki et al, 2000;Reckova et al, 2003;Hall et al, 2004). Earlier work demonstrated dramatic effects on the development of cardiac architecture and coronary vasculature when epicardial differentiation was disturbed (Gittenberger-de Groot et al, 2000;Tevosian et al, 2000;Lie-Venema et al, 2003;Eralp et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recruitment of cardiomyocytes into the Purkinje fiber system has been demonstrated to be related to hemodynamic influences derived from the coronary vasculature and endocardial lining of the ventricular lumen Hyer et al, 1999), with mature ET-1 and the ECE1 metalloprotease as key inductive factors (Takebayashi-Suzuki et al, 2000;Reckova et al, 2003;Hall et al, 2004). Earlier work demonstrated dramatic effects on the development of cardiac architecture and coronary vasculature when epicardial differentiation was disturbed (Gittenberger-de Groot et al, 2000;Tevosian et al, 2000;Lie-Venema et al, 2003;Eralp et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These unique differentiation sites suggested an inductive role both for periarterial and subendocardial EPDCs and for a paracrine signal from the endocardium and arterial beds in the recruitment of cardiomyocytes into the Purkinje fiber network (Gittenberger-de Groot et al, 2003b;Gourdie et al, 2003). Recent experimentation showed that Purkinje fiber differentiation is tightly regulated by hemodynamic alterations, while mature endothelin-1 (ET-1) and ET-converting enzyme 1 (ECE1) were identified as inductive molecules (Takebayashi-Suzuki et al, 2000;Reckova et al, 2003;Hall et al, 2004). Concomitant retroviral expression of mature ET-1 and ECE1 was even sufficient for the ectopic conversion of adjacent cardiomyocytes into Purkinje fibers (Takebayashi-Suzuki et al, 2000).…”
mentioning
confidence: 99%
“…The specialized conduction system of the vertebrate ventricle has been demonstrated to arise from nonspecialized myocytes in a process involving induction by endothelin acting in concert with a locally expressed endothelin converting enzyme (Gourdie et al, 1998;Hyer et al, 1999;Hall et al, 2004). Dysfunction of the specialized cardiac conduction system or the normal patterns of intraventricular depolarization by a wide range of inherited and acquired pathological conditions can result in ventricular arrhythmias and sudden cardiac death (Wenink, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…At the cellular level, efficient impulse propagation through this network is dependent upon the interplay between cell morphology, membrane excitability, and electrical coupling of adjacent cells via gap junctions, the latter of which is the major determinant for rapid and directional conduction (3). Although regulation of early VCS specification and morphogenesis is becoming well understood (4)(5)(6)(7)(8)(9), less is known about how cells of the VCS gain their specialized conduction properties as they mature.…”
mentioning
confidence: 99%